Some Applications of Differential Subordinations and Superordinations and Sandwich Theoresm - Anamaria G. MACOVEI (Journal of Applied Computer Science & Mathematics, 2014)
The notions of differential subordinations and superdinations werw introduces by S.S. Miller and P.T. Mocanu. In this paper we present some applications of differential subordination and superdination using function (f(z)zk)α. A sandwich theorem type results is also given.